Loco-regional intervention for hepatocellular carcinoma - Wan Yee Lau; Eric C.H. Lai (Journal of Interventional Medicine, 2019)
Anatomic location/size and number of lesions, inadequate volume of future liver remnant, or poor coexisting premorbid conditions preclude surgery in the majority of patients with hepatocellular carcinoma (HCC). Liver transplantation can cure some patients with poor liver function, but few patients are eligible because of scarcity of donors. Without specific anti-cancer treatment, the prognosis of HCC is poor. Various locoregional therapies are used to treat patients who are not candidates for surgery, and have emerged as tools for palliation, tumor down-staging, and bridging therapy prior to liver transplantation. Currently, local ablative therapy even competes with partial hepatectomy and liver transplantation as a primary treatment for small HCC. HCC is well suited to treatment with loco-regional therapy because it has a tendency to stay within the liver, with distant metastasis generally occurring late in the course of disease. This suggests that an effective local-regional therapy can have a great impact on HCC patients who are not candidates for surgical treatment. Loco-regional therapy can further be justified because patients with HCC usually die of liver failure consequent to intrahepatic growth resulting in liver tissue destruction, rather than extrahepatic metastases. Keywords: Hepatocellular carcinoma, Hepatectomy, Loco-regional therapy, TACE, Local ablation